Subnational resource curse: do economic or political institutions matter? - Alexander Libman (Frankfurt School of Finance & Management, 2010)
The absence or the presence of the resource curse is often explained by the specifics of political and institutional factors. The aim of this paper is to study this effect looking separately at economic and political institutions and at their interaction. Unlike most empirical papers in the literature, this paper considers the intra-national variation of institutional environment and access to political decision-making, using a dataset of the Russian regions. It shows that subnational variation of the quality of institutions indeed matters for the effects of resources. Economic institutions follow the traditional 'resource curse' results: resources have a negative impact on growth if the quality of institutions is low. On the other hand, increasing level of democracy has negative consequences for regions with substantial resources. Finally, this paper studies the differentiation between the resource-extracting regions and regions, exporting, but not extracting resources, in terms of the conditional resource curse.
Keywords: O13; P28; Q48; 330; subnational variation; conditional resource curse; democracy; economic institutions; transition economies; Dutch Disease; Rohstoffwirtschaft; Institutionalismus; Demokratie; Regionale Disparität; Übergangswirtschaft; Russland